BIOCHEMICAL CHARACTERIZATION OF THE AEROMONAS SPECIES ISOLATED FROM FOOD AND ENVIRONMENT - Awan, Mohammad Bashir; Ahmed, M. Maqbool; Bari, Abdul; Saad, Anwar M. (Pakistan Journal of Physiology, 2015)
Very few studies have been carried out to comprehensively characterize Aeromonas isolates. This study reports biochemical and enzymatic characterization of 60 isolates belonging to seven Aeromonas species. Methods: Seven types of API (Analytab Production Incorporation, France) strips (API 20 E, API 20 NE, Rapid ID 32 E, API 50 CH, ID 32 GN, ID 32 C, Rapid ID 32 A) were used for the biochemical characterization of the isolates. Results & Conclusions: These strips provided an extensive biochemical profile of the isolates. AI 20 E gave reliable results. The H2S tubule of this strip was added with gelatin-cysteine-thiosulfate medium and got excellent results for H2S production from cysteine. Esculin formulation in ID 32 C was proved most reliable as no false positive or as many false positive and false negative results were given by it. All other strips provided test profile and some of the characteristics in them appeared as significant in differentiation of the various species.